Supervisi Program Pendidikan Kepala Madrasah Pada Profesionalisme Guru Di MA Al-Jauharotunnaqiyyah Palas Cilegon - Husni Abdul Aziz; Agus Gunawan; Machum Bachtiar (LPPM IAIN Sorong, 2023)
One of the competencies that the principal must possess is the ability to supervise. Competence in academic supervision, or the capacity of school administrators to offer advice to educators, students, and instructors in order to raise teacher professionalism. Professionalism in the classroom refers to a teacher's capacity to comprehend pupils, plan and carry out instruction, mentor and educate, develop students, and assess their learning outcomes in order to help them realize their potential. In order to determine the planning, execution, and follow-up of the Principal's Supervision Management in Improving Teacher Professionalism at Madrasah Aliyah Al-Jauharotunnaqiyyah Palas Cilegon, this study employs a qualitative approach and the case study technique. The study's findings indicate that: First, planning for the school principal's academic supervision program entails holding supervision preparation meetings, creating supervision instruments, gathering data through class visits, determining the most effective ways to boost or increase teacher professionalism, and preparing the administration required for supervision implementation. Activities for planning supervision involve all educators and teachers. Second, the technical criteria for supervision are used by school principals to implement supervision in accordance with the standards for doing so. Third, provide direct, indirect, and situational coaching to teachers at Madrasah Aliyah Al-Jauharotunnaqiyyah Palas Cilegon in order to build on the academic supervision of the school principal's success in raising teacher professionalism. There was an increase in the professionalism of teachers after carrying out academic supervision by principals both in quality and quantity